Предмет: Алгебра, автор: cr1stal3255

помогите решить выражение

Приложения:

Ответы

Автор ответа: narminmamedzadeh
0

Объяснение:

5b-(45a+5b^2)/b=(5b^2-45a-5b^2)/b=-45a/b=-45×22/330=-3

Автор ответа: Avantgardе
3

\displaystyle 5\cdot b-\frac{45\cdot a+5\cdot b^2}{b}=\frac{5b^{(b}}{1}-\frac{45 a+5b^2}{b}=\frac{5b^2-45a+5b^2}{b}=\frac{-45a}{b}=\\\\=-\frac{45a}{b}

\displaystyle-\frac{45a}{b}\;\;\pi pu \;\; a=22;\;b=330

\displaystyle-\frac{45a}{b}=-\frac{45\cdot22}{330}=-\frac{45}{15}=-3

Ответ: -3

Похожие вопросы